A case of psoriasiform syphilid (from clinical practice) - S. V. Koshkin; T. V. Chermnykh; O. S. Kovrova; N. YU. Ryabov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The current article analyzes a clinical case of general psoriasis-form syphilid in a 28-year patient. Attention is paid to combination of exudative psoriasis and syphilis in in a sex partner. Problems of differential diagnosis for clinical evidence of secondary syphilis and psoriasis were analyzed.